(untitled) (Development Service Industry Management, 2023)
The strategic goal of Ukraine’s integration into the European Union requires the implementation of common principles of applying customs legislation and deepening cooperation in this area to reduce negative impacts and potential risks during control of the movement of goods. The analysis of the practice of their countries is useful for Ukraine, it does not allow to adapt and choose effective directions for improving the national system of European control to the level of European standards, which emphasizes the relevance of this study. The article examines the aspects of integrating European customs control standards in Ukraine and their impact on the country’s customs security. It analyzes the current challenges of the Ukrainian customs system and the necessity of implementing reforms, which include the modernization of the technological base, improving the qualifications of customs officials, and the introduction of advanced information technologies. The adoption of European standards will contribute to reducing the risks of smuggling and customs legislation violations, enhancing the efficiency of customs operations, and the overall economic development of the country. The article emphasizes the importance of international cooperation and technical assistance for the successful implementation of these reforms. The conclusions of the article demonstrate that Ukraine’s integration into the European customs system is a significant step towards strengthening economic stability and development in the country.